High-avidity, high-IFNγ-producing CD8 T-cell responses following immune selection during HIV-1 infection - Keane, Niamh M. (2011)
HIV-1 mutations which reduce or abolish cytotoxic T lymphocyte responses against virus-infected cells are frequently selected in acute and chronic HIV-infection. Among population HIV-1 sequences, immune selection is evident as HLA allele-associated substitutions of amino acids within or near CD8 T cell epitopes. In these cases, the non-adapted epitope is susceptible to immune recognition until an escape mutation renders the epitope less immunogenic. However, several population-based studies have independently identified HLA-associated viral changes which lead to formation of a new T cell epitope, suggesting that the immune responses which these variants or “neo-epitopes” elicit provide an evolutionary advantage to the virus rather than the host. Here, we examined functional characteristics of eight CD8 T cell responses that result from viral adaptation in 125 HLA-genotyped individuals with chronic HIV-1 infection. Neo-epitopes included well-characterised immunodominant epitopes restricted by common HLA alleles and in most cases, the T cell responses against the neo-epitope exhibited significantly greater functional avidity and higher IFNγ production than T cells for non-adapted epitopes but were not more cytotoxic. Neo-epitope formation and emergence of the cognate T cell response co-incident with a rise in viral load was then observed in-vivo in an acutely infected individual. These findings demonstrate that HIV-1 adaptation not only abrogates immune recognition of early targeted epitopes, but may also increase immune recognition to other epitopes, which elicit immunodominant but non-protective T cell responses. These data have implications for immunodominance associated with polyvalent vaccines based on the diversity of chronic HIV-1 sequences.